Paint Recipe Book - Wagstaff, Liz (London Quadrille Publ., 2000)
A sourcebook for home decorators and a reference work of paint effects and their application. It includes over 50 separate techniques for walls, wood, stone and metal, as well as for plastic and other synthetic surfaces. Altogether, there are over 150 "recipes" with easy-to-follow instructions.
Include Color Illustration and Index
Keywords: Interior decoration -- Paint mixing -- House painting